LINGUISTIC SEXISM IN THE IRANIAN HIGH SCHOOL EFL TEXTBOOKS - Vahdatinejad, Shapour (PEOPLE: International Journal of Social Sciences, 2017)
As it is noted by the Iranian Ministry of Education, the number of female school students is almost equal to that of the males. Since textbooks are the only resource for majority of both teachers and students therefore, unbiased textbooks are necessary for students to build up their role in addressing the other gender in their lives and society. Therefore, this study attempted to explore the status of linguistic sexism in the current Iranian high school EFL textbooks (four volumes) published by the Ministry of Education in 2014. This study is a quantitative content analysis to investigate whether both genders (in terms of pronouns, title names and firstness) have been addressed equally or not. Having digitalized the textbooks, WordSmith Tool 4 tabulated the data in numbers then the raw data was transformed into percentages. The results highlighted that males are mostly the focal characters in the texts. The findings also show that male related pronouns ‘He’ and ‘his’ outnumbered females by the ratio of 2 to less than 1. The roles of females and their realistic contributions to the society are not well represented in the textbooks. Some implications are advised for teachers, textbook writers and policy makers.